2011
DOI: 10.1162/jocn.2010.21594
|View full text |Cite
|
Sign up to set email alerts
|

Intention Processing in Communication: A Common Brain Network for Language and Gestures

Abstract: Abstract■ Human communicative competence is based on the ability to process a specific class of mental states, namely, communicative intention. The present fMRI study aims to analyze whether intention processing in communication is affected by the expressive means through which a communicative intention is conveyed, that is, the linguistic or extralinguistic gestural means. Combined factorial and conjunction analyses were used to test two sets of predictions: first, that a common brain network is recruited for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 71 publications
6
66
3
Order By: Relevance
“…Our findings suggest that the fusiform area might support internal representations at least at an early perceptual level. That BA18 and BA19 within the occipital lobe are involved in the ToM task is in line with some other literature showing a role for occipital cortex in ToM tasks (Enrici et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings suggest that the fusiform area might support internal representations at least at an early perceptual level. That BA18 and BA19 within the occipital lobe are involved in the ToM task is in line with some other literature showing a role for occipital cortex in ToM tasks (Enrici et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…The AI task is a novel video version of a cognitive ToM task previously used in a comic strips form55565758. The AI task was a story completion task in which participants were asked to demonstrate their comprehension of the stories by choosing the most appropriate story endings.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has noted difficulty on tasks requiring inference-making such as Theory of Mind (Adenzato et al, 2010; Gregory et al, 2002; Pardini et al, 2013; Torralva et al, 2007) and fMRI studies of social cognition have implicated vmPFC in Theory of Mind measures (e.g., Amodio & Frith, 2006; Enrici, Adenzato, Cappa, Bara, & Tettamanti, 2011; Frith & Frith, 2006; Mitchell, 2009; Saxe, 2006; Van Overwalle & Baetens, 2009). Taken together, these findings appear to suggest that vmPFC disease in patients with bvFTD compromises the inference-making component of their social interactions.…”
Section: Methodsmentioning
confidence: 99%
“…These patients have difficulty on tasks requiring inference-making such as Theory of Mind (Adenzato, Cavallo, & Enrici, 2010; Gregory, Lough, Stone, & Erzinclioglu, 2002; Pardini et al, 2013; Torralva et al, 2007), although inference-making has rarely been assessed explicitly. Nevertheless, imaging studies (Adenzato, Cavallo, & Enrici, 2010; Eslinger et al, 2007; Gregory, Lough, Stone, & Erzinclioglu, 2002; Grossman, 2007; Grossman et al, 2010; Kipps & Hodges, 2006) and autopsy reports (e.g., Brettschneider et al, 2014; Hu et al, 2007) have shown that bvFTD affects dorsolateral, ventral and medial regions of the frontal lobe, and these regions have been implicated in several fMRI studies of social cognition (e.g., Amodio & Frith, 2006; Enrici, Adenzato, Cappa, Bara, & Tettamanti, 2011; Frith & Frith, 2006; Mitchell, 2009; Saxe, 2006; Van Overwalle & Baetens, 2009) and reasoning (e.g., Bhatt, Lohrenz, Camerer, & Montague, 2010; Meghana Bhatt & Camerer, 2005; Coricelli & Nagel, 2009; Goel, 2007; Prado & Noveck, 2007; Prado et al, 2014; Rypma, Berger, & Genova, 2005). …”
Section: Introductionmentioning
confidence: 99%